Decolourization of reactive red 120 dye using Z11-AI-CO3 layered double hydroxide / Hairul Safley Hamdan - Hamdan, Hairul Safley (Faculty of Applied Sciences, 2009)
The application of Layered Double Hydroxides (LDHs) as adsorbent removal of Reactive Red 120 from aqueous solutions at various parameters. These include initial concentration, contact time, temperature, pH and different adsorbent dosage. The adsorption isotherms could be defined with Langmuir Model and Freundlich model. Characterization of Layered Double Hydroxides using X-Ray Diflfractogram showed the presence sharp peaks which signifying high crystallinity. The presence of sharp and intense lines is indicated with dspacing of 7.9 A. Adsorption experiments confirmed that layered double hydroxide was effective in uptake of Reactive Red 120 from aqueous solution.